(untitled) (Web of Teachers: Inderscience Research, 2026)
The article analyzes the role of literacy competence in the educational process, the importance of new generation textbooks, and the modern approaches used in them. Literacy competence is closely related not only to learning to read and write, but also to the development of independent thinking, analysis, and communication skills in education.